ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 MENGENAI ANAK LUAR KAWIN PERSPEKTIF UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK DAN HUKUM ISLAM - Megawati, Megawati (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
After the issuance of the decision of the Constitutional Court Number  46/PUU-VIII/2010, Article 43 of Law Number  1Year 1974 concerning Marriage which originally stated that the married child has only a civil relationship with his mother and his mother’s  family, has blood  relation  including  civil relationship with father his biological and his father’s family although there  must  be recognition or can  be proven  on the basis  of science and  technology and/or  other  evidence. The decision of the Constitutional Court can  be seen from two sides,  namely  the protection of the rights of the married child, and  the conformity  of the  understanding of the  child outside of marriage according to Islamic  law, because according to Islamic law the  child outside marriage should  not at all have  a nasab relationship with his biological  father.  Based  on the  above background, this research reveals  two issues,  firstly how the legal power  of the Constitutional Court decision regarding the outsider marriage perspective of Law Number  35 year 2014 on Child Protection. Second, what is the conformity between the Constitutional Court decision No. 46/PUU-VIII/2010 concerning the married child against the provision of an outsider from the perspective of Islamic law. This type of research is normative juridical research or library research which  is then described descriptively.  The results of this study conclude that the legal force of the Constitutional Court decision is binding (final and binding).  Recognition  of the rights of children  outside marriage shall be exercised by all parties  concerned, in accordance with Article 59 paragraph 2 letter o Law No. 35 of 2014 on Child Protection, that every child has the right to survival, growth and development and is entitled to protection from violence and discrimination, including special protection to children  who are victims of stigmatization from labeling related to the condition of their parents. Meanwhile,  if you look at the provisions in Islamic law, the decision of this Constitutional Court should be adjusted to the understanding of children  outside marriage in Islamic law, because the Constitutional Court decision is a law made man,  while Islamic law is a law that comes from Allah SWT. It is also important to revise Article 2 paragraph (2) on the provision of marriage registration as a legal marriage requirement to be only an administrative requirement. “Outer Child Marriage, Constitutional Court and Islamic Law”.